Volumetric Method for Free and Total Glycerin Determination in Biodiesel - Pisarello Milesi, Maria Laura (2010)
In the last few years, biodiesel has gain considerable attention due to the increasing concern for the environmental problems associated with the use of fossil fuels. The quality control of this renewable fuel involves numerous analyses, several of them requiring the use of analytical instruments. According to ASTM and EN standards, the analyses of free and total glycerin which are of particular relevance to biodiesel quality must be carried out by GC analysis. This work presents an alternative volumetric method, which does not need expensive equipment, and is therefore particularly useful for quality control in small facilities. Another advantage of the proposed method is that it also overcomes the shortcomings of the GC procedure, such as detection limits and type of raw material used to produce biodiesel. While the GC analysis is restricted to biodiesel obtained from soybean, rapeseed or sunflower oil, the volumetric method has no limitations in this sense.